Initial Management Pre Hospital: A Systematic Review - Rizky Rachmatullah; Sriyono Sriyono; Hakim Zulkarnain (GLOBAL HEALTH SCIENCE GROUP, 2025)
Early management in the pre-hospital phase plays a crucial role in the emergency medical service system. Quick, accurate, and targeted interventions can prevent patient deterioration, reduce mortality rates, and improve clinical outcomes. This phase begins with the initial assessment, which serves as the foundation for determining the priority of medical interventions. This review aims to identify and analyze various literatures related to the strategies of early management applied to patients in pre-hospital care settings. Method: A systematic review was conducted by searching five major databases: PubMed, ScienceDirect, Scopus, Google Scholar, and ProQuest. The search was limited to publications from 2019 to 2024 using keywords such as “initial management,” “pre-hospital care,” and “emergency patient”. A total of 88 articles were obtained, while 16 articles that met the inclusion criteria were analyzed descriptively. The review indicates that structured and evidence-based early management in the pre-hospital phase can improve handling efficiency, accelerate intervention time, and reduce the risk of complications in emergency patients. Medical personnel skills, clear protocols, and a well-established coordination system are key factors for success. Early management in the pre-hospital phase is a crucial part of the emergency medical system. Optimal implementation based on scientific evidence can improve service quality and have a positive impact on patient safety and prognosis.